Political Lobbying Walhi terhadap Krisis Banjir Bandang di Sumatera - Neima Aulia; Ahmad Mujammil Raza; Aditia Saputra; Winda Dwi Astuti Zebua (Institut Nalanda, 2026)
The Indonesian Forum for the Environment (WALHI) responded to the flash flood crisis in Sumatra at the end of 2025. The floods were triggered by massive deforestation and the failure of environmental governance, highlighting the urgency of shifting the paradigm from an anthropocentric discourse (natural disasters) to an ecocentric one (ecological disasters). This study aims to analyze how WALHI utilized the momentum of the crisis to reframe public discourse while also using it as an effective political lobbying tool. The research methods used were descriptive qualitative and data analysis of conventional media (framing) and documentation. The results of the study found that WALHI implemented an integrated public affairs strategy. By shifting the public narrative through media campaigns, it then translated this into political pressure through direct lobbying of the Ministry of Forestry and Commission IV of the Indonesian House of Representatives. This strategy succeeded in pushing for concrete policies such as the revocation of 22 forest management permits and the formation of an investigative working committee in the House of Representatives. The research findings offer an integrative advocacy model for civil society organizations, showing that a combination of effective discourse framing and structured political lobbying can transform ecological crises into substantive policy changes.